Les rumeurs de l’oubli dans les romans de Sylvie Germain ou l’exploration germanienne de l’hypomnésie - Anne-Claire Bello (Les Cahiers de Framespa)
In Memory, History, Forgetting, Paul Ricoeur analyzes the use and abuse of memory, which, he says, « are also abuses of forgetfulness ». A selective discourse expats everything that is likely to undermine the dominant ideology. Sylvie Germain’s novels explore these « abuses of forgetting » : the forgetfulness commanded by amnesty policies ; the forgetting imposed by the policies of censorship and confiscation of testimony ; the oblivion orchestrated by the occultation of memory. The work attempts to decipher the mechanisms of this occultation which consists not only in hiding reality but in erasing all trace of this reality in the memory of later generations. We propose to observe how Sylvie Germain reflects in her novels on the usages and abuses of oblivion, how her imagination explores mechanism of hypomnesy and occulted memory.